Goddesses and the divine feminine : a Western religious history - Ruether, Rosemary Radford (University of California Press, 2005)
Rosemary Radford Ruether presents an illuminating portrait of goddesses and sacred female imagery in Western culture, from prehistory to contemporary goddess movements.